Banda Taiyō Ongaku-tai: ressonâncias da cultura Sōka no “sertão do Caicó” - Maia, Alexandre Fernandes (2022)
Research participant of immersion about "Taiyō Ongaku-tai [Sun Musical Band]", funded in 1991, in the city of Caicó, in the countryside of the State of Rio Grande do Norte, Brazil. It is about a youth male community of musical practice, linked to Brasil Sōka Gakkai Internacional (BSGI), emerged in the middle of 20th century and oriented by Nichiren Buddhism. By ethnomusicological perspective, this study aims to document the emer- gence, establishment, maintenance and adaptation of this community, observing the cultural behavior of the social actors while musicians and supporters of this SGI neo-buddhism. First, this thesis situates the genesis of the BSGI and the Ongaku-tai Band, since its early days in Japan until its transculturation in Brazil, including the northeast region. The musical band creates one of the strategies of cohesion, dissemination and continuity of the values of the Sōka Culture. In the narratives of this group, constantly resonates words as "bringing hope and cour- age through the music". By dialoging with studies about bands and about BSGI and being this in- stitution, an ideology that emigrates from Japan to Brazil, we aim that the present research can align to the reflections of broader references, like the conduct of the social minorities between places, of intercultural and translocal contexts.